Comparative Analysis of Imaging Modalities for Surveillance on Outcomes in Patients With Hepatocellular Carcinoma - Ahmed El Sabagh; Islam Mohamed; Mazen ElSheikh; Megha Bhongade; Eunji Jo; Susan G. Hilsenbeck; Fasiha Kanwal; Prasun K. Jalal (Gastro Hep Advances)
Background and Aims: The American Association for the Study of Liver Diseases recommends regular surveillance with ultrasonography (US) and alpha-feto protein every 6 months for patients at high risk of hepatocellular carcinoma (HCC). However, US is considered to be less effective than cross-sectional imaging modalities like computed tomography and magnetic resonance imaging for detecting early HCC. Limited data exist on the overall survival and receipt of curative treatment for patients undergoing surveillance with different imaging modalities. Methods: We retrospectively reviewed patients (n = 1954) diagnosed with HCC between January 2011 and June 2021. Patients who developed HCC while on strict semiannual surveillance were included in the study. We estimated survival using the Kaplan-Meier method and compared the outcomes on different modalities of imaging using the Log Rank test. We used univariate and multivariate Cox model to evaluate factors affecting survival. Results: A total of 183 patients developed HCC on semiannual surveillance with Imaging (115 with contrast-enhanced magnetic resonance imaging, 34 with multiphasic computed tomography and 34 with US) and alpha-feto protein. No significant difference was noted in overall survival or transplant-free survival based on the imaging modality employed for surveillance for at-risk patients. No correlation was found between the type of imaging modality for surveillance and receipt of curative treatment. Conclusion: Using surveillance program rigorously in at-risk patients, we did not find any association between the imaging modality and clinical outcomes in patients with HCC. It is likely that adherence to surveillance program irrespective of imaging modalities is more effective to influence the outcome, but it needs further studies.